Technical note: modified duration in case of effective IRR - Valenzuela O., Jaime (Estudios de Administración, 2007)
The objective of this technical note is to clarify how Macaulay’s duration should be modified when the internal rates of return (IRR) on fixed income financial assets are expressed in terms of aneffective annual rate. In Chile the usual market practice is to utilize effective IRR, and it leads to an error when modifying Macaulay’s duration using the usual textbook formula (simple TIR). Thistechnical note demonstrates mathematically the correct formula to modify duration for the case of effective IRR.